Karakteristik Marshmallow Carica (Carica pubescens L.) dan Sari Wortel (Daucus carrota L.) dengan Perlakuan Penambahan Gelatin dan Putih Telur - Monicha Raeatya; Rosida Rosida (G-Tech: Jurnal Teknologi Terapan, 2024)
This research aims to determine the effect of the addition gelatin and the addition egg white on the characteristics of marshmallows. The method used was a completely randomized design (CRD) with two factors. The first factor was the addition of gelatin (8%, 10%, 12%) and the second factor was the addition of egg white (6%, 8%, 10%). The results showed that the addition of gelatin and egg white had an effect on water content, ash content and hardness, but had no effect on antioxidant activity, vitamin C and reducing sugars. The best research results were marshmallows with the addition of 12% gelatin and the addition of 10% egg white which produced marshmallow characteristics with a water content of 19,98%, ash content of 0,23%, antioxidant activity of 29,64%, vitamin C of 13,10mg/100ml, reducing sugar 8,36%, hardness 1,06 N and organoleptic test showed color 3,76; taste 4,20; aroma 3,60; and texture 4,04.